Mata Uang Kripto: Apakah Sebuah Jawaban Gaya Hidup Gen Z? - Palupi, Shara Merry; Putranti, Ellyn Citra (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
Gen “Z” is known for their ability to utilize technology that can be implemented in financial investment. This capability is what motivates Gen